Maximum Likelihood Estimates of a Partial Adjustment-Adaptive Expectations Model of the Demand for Money - Thornton, Daniel L. (The Review of Economics and Statistics, 1982)
Daniel L. Thornton, Maximum Likelihood Estimates of a Partial Adjustment-Adaptive Expectations Model of the Demand for Money, The Review of Economics and Statistics, Vol. 64, No. 2 (May, 1982), pp. 325-329